UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN EVERYONE IS TEACHER HERE PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DI KELAS VIII SMP - Sarumaha, Edita (Universitas Nias Raya, 2023)
The problem in this research is that students' enthusiasm for learning begins to decline, students lack the courage to submit questions or opinions to subject teachers during learning activities. The purpose of this study was to improve student learning outcomes through the Everyone Is Teacher Here learning model in Pancasila and civics education subjects in class VIII SMP Negeri 1 Toma in the 2022/2023 Academic Year. This type of research is classroom action research (CAR). The subjects in this study were class VIII students of SMP Negeri 1 Toma with a total of 24 students. The results showed that students were able to increase their enthusiasm for learning and were able to participate in giving responses and questions both to the teacher and to their friends. Based on the average value of the research results in cycle I was 62.4 with the number of students who completed as many as 8 (eight) people with the results obtained was 33.3% and those who did not complete their studies were 16 (sixteen) people with the results obtained was 66.7 %. Whereas in cycle II with an average score of 78.7 where all students complete learning as many as 24 (twenty four) people with the result obtained is 100%. Suggestions that can be submitted by researchers are 1) For teachers, teachers should use the Everyone Is Teacher Here learning model, in the student learning process activities so that they are able to improve student learning outcomes and participate in expressing opinions and questions to their classmates. 2) For students, with the Everyone Is Teacher here learning model used by Pancasila and civics education subject teachers, it can improve the quality of learning so that students' enthusiasm for learning is better and they are able to have the courage to express opinions.